2005
DOI: 10.1111/j.1600-6143.2005.00742.x
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of BK with Tacrolimus Versus Cyclosporine and Impact of Preemptive Immunosuppression Reduction

Abstract: Our purposes were to determine the incidence of BK viruria, viremia or nephropathy with tacrolimus (FK506) versus cyclosporine (CyA) and whether intensive monitoring and discontinuation of mycophenolate (MMF) or azathioprine (AZA), upon detection of BK viremia, could prevent BK nephropathy.We randomized 200 adult renal transplant recipients to FK506 (n = 134) or CyA (n = 66). Urine and blood were collected weekly for 16 weeks and at months 5, 6, 9 and 12 and analyzed for BK by polymerase chain reaction (PCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
680
14
28

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(795 citation statements)
references
References 16 publications
58
680
14
28
Order By: Relevance
“…Previously, Kamar et al noted that BK virus was the most common virus detected in RTX-treated patients [8], and Habicht et al found a nonsignificantly higher rate of BK in ABO-incompatible recipients administered RTX [11]. The rates of BK viremia and nephropathy in our cohort are congruent with rates previously reported in the renal transplant population [18][19][20][21]. However, viremia and nephropathy occurred 2-3x more often in the RTX cohort.…”
Section: Discussionsupporting
confidence: 81%
“…Previously, Kamar et al noted that BK virus was the most common virus detected in RTX-treated patients [8], and Habicht et al found a nonsignificantly higher rate of BK in ABO-incompatible recipients administered RTX [11]. The rates of BK viremia and nephropathy in our cohort are congruent with rates previously reported in the renal transplant population [18][19][20][21]. However, viremia and nephropathy occurred 2-3x more often in the RTX cohort.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, BK viremia prevalence was 18% [20]. This is consistent with the described incidence of BK viremia in renal transplant recipients (10-20%; [8,23]) Importantly, we choose to intervene at plasma BKV loads of log 3 or greater. This value was chosen as the lower limit of detection for a "positive" result using our assay.…”
Section: Discussionsupporting
confidence: 64%
“…The mainstay of treatment for BK viremia/nephropathy has been reduction of immunosuppression [8]. Unfortunately, the development of BK nephropathy carries with it a significant rate of graft dysfunction/ loss [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those and other studies, viremia cleared in 92%e95% of patients, with a mean time to clearance of 54 days [18,19]. In contrast, rejection rates of up to 30% have been reported with reduction in immunosuppression alone, and allograft loss of 35%e50% despite reduction in total immunosuppression [20,21].…”
Section: Treatmentmentioning
confidence: 69%